Pengembangan Video Lobang Jepang Padang Besi: Media Promosi Wisata Sejarah - Apriyanti, Difiani -; Wahyuni, Nini; Djonnaidi, Silvia; Telaumbanua, Yohannes; Laily, Hamidah Izzatu (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
The community service which partner with Padang Basi district is aimed to support the promotion of the new historical tourism destination namely Lobang Jepang Padang Basi. By the cooperation between Padang Education and Culture official and Mapastra FIB Unand, this tourism place has been sucessfully reopenned for public. Beside having historical value, there is also a tunnel and five square bunkers in box shaped embedded under the ground. Looking at the potential of this tourism place, the community service team creates video of Lobang Jepang Padang Basi which can be beneficiary as an information and promotion media. Furthermore, the content of the video can be used as society education media that presents the historical struggle of Minangkabau people in fighting against Japanese colonialism. The activities of community service consist of three steps which are planinng, implementation, and evaluation. While, the video making consists of pre-production, production, and post-production. It is hoped that the customer service activities can give a positive contribution for Padang Basi district and can be usefull for many people.